Simulation Based Performance Assessment of Developing Heterarchical Control for a Flexible Assembly System - Ismayyir Dhuha Kadhim; AL-Khafaji Mohanned.M.H.; Dawood Lamyaa M. (Management Systems in Production Engineering, 2025)
In order to increase the robustness and flexibility of manufacturing systems under dynamic conditions which represented by disturbances that caused by uncertainties in customer demand, the heterarchical control multiagents’ system is increasingly being applied. Heterarchical model adopt the structure which has no centralized control as the agents in heterarchical model are distributed connected in a peer relation. The paper examines the developed heterarchical control multi-agents’ system in flexible assembly system, demonstrates its feasibility by simulation. The purpose of this study is to assess and enhance the efficiency, adaptability, and overall efficacy of the control system. This assessment is crucial for ensuring that the system can effectively manage dynamic and sophisticated situations. Production control model based on heterarchical structure was developed by utilize the MATLAB/SIMULINK software package, and look at the effects of changes on the manufacturing environment, specifically how changes in consumer demand in term of quantity and variety that affects the model. The process entails developing a computational model that imitates the behavior of the heterarchical control system in order to predict results. The simulation procedure included specifying the parameters and initial conditions of the system, executing the simulation, and assessing the outcomes. The results indicated a rise in throughput as well as an increase in the utilization of both the machine and material, as well as reduction in cycle time by facilitating quicker modifications to processes. The implemented approach resulted in an increase in the profitability of the manufacturing firm, meeting customer demand that making it more competitive in the marketplace.